Uji Aktivitas Sitotoksik Fraksi Daun Matoa (Pometia pinnata) dengan Metode Brine Shrimp Lethality Test (BSLT) - Risma Payung; Elsye Gunawan; Rani D. Pratiwi (Jurnal Biologi Papua, 2021)
Matoa (Pometia pinnata) is parts of Sapindaceae family widely spread in tropical areas, especially in Papua. Several studies mentioned the use of its parts as antioxidants and contain phenolic compounds and flavonoids. This study aim(s) to conduct a phytochemical screening test as well as a cytotoxic test for Pometia pinnata leaves fraction using the BSLT method. The research series began with the extraction process using 96% ethanol, then fractionated using three solvent variations: n-hexane, ethyl acetate, and ethanol. Further, the phytochemical screening test was carried out for cytotoxic testing in order to see the mortality rate of shrimp larvae Artemia salina Leach. The result of the phytochemical showed that the secondary metabolite compounds on the ethanol and ethyl acetate fraction were alkaloids, flavonoids, saponins, tannins, and terpenoids compounds meanwhile the n-hexane fraction contained terpenoids. The results of cytotoxic testing BSLT showed the LC50 value in the n-hexane was 7029.10 ppm, 406.07 ppm for ethyl acetate and 614.47 ppm for ethanol. Thus, it could be said that ethyl acetate and ethanol fractions were classified as a toxic category, while n-hexane was classified as a non-toxic category.Key words: matoa; fraction; phytochemical screening; cytotoxic.